0
$\begingroup$

given $y_1 = x$ and the equation: $x^3y'''-3x^2y''+(6-x^2)xy'-(6-x^2)y = 0$

I determined $y_2 = ux$,

$y_2' = u+xu'$,

$y_2''= 2u'+xu''$,

and $y_2'''= 3u''+xu'''$

substitution in the equation gives me: $x^4u'''-x^4u' = 0$

then, let $v=u'$, $v'=u''$, and $v''=u'''$ gives me $x^4v'' - x^4v = 0$

how do you go about solving after that? i believe it has to do with separable equations, but i can not figure it out. HELP PLEASE!!!

$\endgroup$
  • $\begingroup$ You have $v''=v$, which has solution $C_1e^{-x} + C_2e^x$. $\endgroup$ – Chee Han Dec 1 '16 at 6:45
0
$\begingroup$

You properly did the work and assuming $x\neq 0$, your last equation write $$v''-v=0$$ which cannot be reduced anymore.

The characteristic equation being $r^2-1=0\implies r=\pm 1$, then the general solution is given by $$v=c_1 e^x+c_2 e^{-x}$$ which makes $$u=c_1 e^x-c_2 e^{-x}+c_3$$ and $$y=x(c_1 e^x-c_2 e^{-x}+c_3)$$ SInce we use constants, change $-c_2$ to $c_2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.